PENGARUH LINGKUNGAN KERJA, PEMBERDAYAAN, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi di PT.Phapros,Tbk Semarang) - Anissa Nur Safitri; Kasmari Kasmari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The importance of evaluating performance is a reference for empowering human resources, to assess how far an institution is supported by the strength of its human resources and knowing the results. Without an assessment of the performance of an organization/institution, the organization will not know how much it has achieved based on the resources it has. This type of research uses quantitative data. The population in this study amounted to 150 permanent employees at PT. Phapros, Tbk. Semarang. In this study, the sample as well as respondents to the questionnaire were 60 respondents. The sampling technique used was random sampling. Data obtained through questionnaires.The results of the research conducted indicate that : (1) Work environment has a positive and significant impact on employee performance. (2) Empowerment has a negative but significant effect on employee performance. (3) Leadership has a positive and significant effect on the performance of employees of PT. Phapros, Tbk Semarang.